Targeting Dendritic Cells in vivo for Cancer Therapy - Caminschi, Irina; Maraskovsky, Eugene; Heath, William R. (Frontiers in Immunology, 2012)
Monoclonal antibodies that recognise cell surface molecules have been used deliver antigenic cargo to dendritic cells (DC) for induction of immune responses. The encouraging anti-tumour immunity elicited using this immunisation strategy suggests its suitability for clinical trials. This review discusses the complex network of DC, the functional specialisation of DC-subsets, the immunological outcomes of targeting different DC-subsets and their cell surface receptors, and the requirements for the induction of effective anti-tumour immunity. Finally, we review preclinical experiments and the progress towards targeting human DC in vivo.